(3JNGejS GdgeRjI aj eOM NjQ GdHQjI ddEeGe GdHhUjQis - (3eMeO Hf edG CMeO CMeO GdMGaXs; (3GdHhUjQj,J (B696 (3g` s
(3ChdgG (B:s
1-(3TgGH GdOjf CMeO GdNGdOi(B: (3cfJ fhQ hcGf Ke YeGA hfHjG hdjS Wjf heGA s
(3BNQgG (B:s
(3eG CbGe GddGI ef YHO Gddg hbGeJ HQHgG GdCTjGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GfXQgG eY eLehYI JSGHjY hJNGejSs
(3hgj KdGKI YTQ JNejSG deDdajf eNJdbjf JSYI efgG JCJi ChdkG Ke HYO EfJgGFgG JCJi CQHYI JNGejS CNQis
(3hcJHJ GdJNGfjS ai eQHYGJ Edi LhGQH HYVgG GdHYV Ke jCJi JMJ GdJNGejS HjJ ef CHjGJ GdgeRjIs
(3JHUQI GdYfhGf (B:s
(3JNejS TYQis
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs